ANALISIS SENTIMEN TERHADAP APLIKASI LINKAJA MENGGUNAKAN METODE NAÏVE BAYES CLASSIFIER - Sitepu, Marheni; Yohanna, Margaretha; Manurung, Samuel Van Basten H. (Universitas Methodist Indonesia, 2024)
Electronic money is increasing, causing more and more service innovations to emerge. People carry out online transactions using electronic technology, or Fintech. The fintechs widely used today are e-wallets or digital wallets such as Dana, Ovo, LinkAja, etc. In this research, LinkAja as a fintech application will be analyzed using 100 review data samples and summarized into two classes: positive and negative. This research was carried out using the Naïve Bayes Classifier classification method. Sentiment analysis of reviews on the LinkAja application obtained results of 75% accuracy, 83% Precision, 75% Recall, and 73% F1_score.